2021
DOI: 10.1186/s40644-021-00397-4
|View full text |Cite
|
Sign up to set email alerts
|

The value of contrast‐enhanced ultrasound in determining the location of sentinel lymph nodes in breast cancer

Abstract: Background This study aimed to explore the sentinel lymph node (SLN) identification rate in breast cancer by subcutaneous and intradermal injection of ultrasound contrast agent in the mammary areola region, compared to the results achieved with methylene blue (MB). Methods A total of 390 breast cancer patients with planned sentinel lymph node biopsy from our breast surgery department from July 2017 to February 2019 were enrolled. All patients were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 18 publications
3
8
0
Order By: Relevance
“…In our study, the average number of SLNs identified by CEUS per patient was significantly less than those detected by MB (Z = −11.37, p < 0.001), which is also reflected in the results of other related studies [18,20]. MB, as small molecules, tend to diffuse into secondary lymph nodes, or dye spillage causes blue staining of the tissue and lymph nodes around SLNs, making it difficult to distinguish real SLN from non-SLN.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…In our study, the average number of SLNs identified by CEUS per patient was significantly less than those detected by MB (Z = −11.37, p < 0.001), which is also reflected in the results of other related studies [18,20]. MB, as small molecules, tend to diffuse into secondary lymph nodes, or dye spillage causes blue staining of the tissue and lymph nodes around SLNs, making it difficult to distinguish real SLN from non-SLN.…”
Section: Discussionsupporting
confidence: 80%
“…Therefore, we hypothesized that patients who failed to trace SLN with CEUS had little chance of successful intraoperative tracing. Meanwhile, it has been shown that CEUS could identify SLN that could not be detected by blue staining, further proving that CEUS is a simple and highly reproducible SLN tracer technology [20].…”
Section: Discussionmentioning
confidence: 99%
“…However, many studies have confirmed that CEUS could be used to identify and locate SLN of breast cancer safely 14–20 . Besides, our previous research also confirmed its feasibility 21 …”
supporting
confidence: 67%
“…[14][15][16][17][18][19][20] Besides, our previous research also confirmed its feasibility. 21 At present, there are many studies on the evaluation of breast cancer SLN metastasis by CEUS, but only few studies have been done on lymphatic drainage pattern (LDP). 16,22,23 This study focuses on analyzing the basic characteristics of SLN and SLC in breast cancer and summarizing the LDP to improve the accuracy of SLNB.…”
mentioning
confidence: 99%
“…Studies on the effectiveness of the ABUS in the prediction of breast cancer have been conducted in recent years. These results showed that the detection rate, sensitivity, and specificity of ABUS in the diagnosis of breast cancer are more than that of MTR, but whether it is higher than HHUS is still controversial [6][7][8]. Some studies showed that ABUS and HHUS did not show considerable differences in prediction of cancer in breast and specificity, detection rate, and sensitivity [9].…”
Section: Introductionmentioning
confidence: 97%